STRATEGI PEMENANGAN CALON KEPALA DESA INCUMBENT PADA PEMILIHAN KEPALA DESA KUTA SAGA KECAMATAN KERAJAAN KABUPATEN PAKPAK BHARAT PROVINSI SUMATRA UTARA TAHUN 2018 - Cibro, Komala Fitriani; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Kuta Saga Village is the oldest village in the Royal District of Pakpak Bharat Regency, North Sumatra Province which is led by a female village head. His leadership has lasted for 3 periods as head of Kuta Saga village. The current village head in Kuta Saga village is able to hold the position of village head for three consecutive terms, of course, requires a strategy to be able to maintain his position.                This study is to find out how the strategy of winning the incumbent village head candidate in the election of the Kuta Saga village head, Kerajaan sub-district, Pakpak Bharat district, North Sumatra province in 2018 and what are the factors that led to the election of Marlina Boangmanalu as the Head of Kuta Saga Village, Kerajaan District, Pakpak Bharat Regency, Sumatra Province. North 2018. This study uses a qualitative approach with a descriptive method. The types of data in this study are primary data and secondary data. Data collection techniques in this study were interviews and documentation.                The results of this study indicate that the strategy for winning the incumbent village head candidate in the Kuta Saga village head election, Kerajaan sub-district, Pakpak Bharat district, North Sumatra province in 2018 consists of offensive and defensive strategies. The approach, the figure of the success team, the clan factor and money politics were the success factors for Marlina Boangmanalu in obtaining votes in the 2018 Kuta Saga village head election.  Keywords : Strategy, Incumbent, Village Head Election